PERAN SEKTOR INFORMAL TERHADAP PEREKONOMIAN DAERAH: PENDEKATAN DELPHI-IO DAN APLIKASI - Tri Widodo (Journal of Indonesian Economy and Business (JIEB), 2006)
This paper analyzes theoritically and empirically the role of informal sectors on the local economic development. In general, the local governments do not put the informal sectors as a focus of the local economic development. Regular data collection regarding to the informal sectors is almost unavailable. This paper derives a method in analysing the role of the informal sectors in local economy by combining quantitative (non survey) and qualitative (survey) method. Input-Output (IO) Table analysis is applied. Survey (Delphi method) is conducted to get the information about the contribution of the informal sectors. This information is used to derive the Input-Ouput Table (IO*) which put into account the role of the informal sectors. Therefore, some parameters (multipliers and linkages) calculated from IO and IO* are compared. This paper applies the method to look at Daerah Istimewa Yogyakarta (DIY) as a case study. Some conclusions are withdrawn in the case of DIY: first, the informal sectors give a positive contribution to local economic development in terms of output, income, employment and sectoral linkages. Second, the role of informal sectors has to be limmited in some certain level.